Respuesta :
The general equation of a line is y = mx +b.
m is equal to the slope, so for this problem it is m = -3
b is equal to the y-intercept (the y-point when x = 0) so according to this since it passes through (0, -2), x=0 at y = -2
The equation of the line is: y = -3x - 2
m is equal to the slope, so for this problem it is m = -3
b is equal to the y-intercept (the y-point when x = 0) so according to this since it passes through (0, -2), x=0 at y = -2
The equation of the line is: y = -3x - 2
since y =mx + c
the coordinates are (x,y) so we can substitute them into y =mx +c
also -3 can be written as -3/1 or 3/-1
(-2) = -3/1 (0) +c
rearranging for c
-2 = c ( since -3/1 multiplied by 0 = 0)
we can now say y = -3/1 x + (-2) which simplifies to y= -3/1 x - 2
the coordinates are (x,y) so we can substitute them into y =mx +c
also -3 can be written as -3/1 or 3/-1
(-2) = -3/1 (0) +c
rearranging for c
-2 = c ( since -3/1 multiplied by 0 = 0)
we can now say y = -3/1 x + (-2) which simplifies to y= -3/1 x - 2